2018
DOI: 10.1371/journal.pone.0209695
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution magic angle spinning NMR studies for metabolic characterization of Arabidopsis thaliana mutants with enhanced growth characteristics

Abstract: Developing smart crops which yield more biomass to meet the increasing demand for plant biomass has been an active area of research in last few decades. We investigated metabolic alterations in two Arabidopsis thaliana mutants with enhanced growth characteristics that were previously obtained from a collection of plant lines expressing artificial transcription factors. The metabolic profiles were obtained directly from intact Arabidopsis leaves using high-resolution magic angle spinning (HR-MAS) NMR. Multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…In our earlier metabolomics study of the VP16-02-003 and VP16-05-014, eighteen biomarkers were identified at t = 6 hours after the start of the light period [8]. In the present study, the rhythm of these biomarkers is followed during the circadian cycle.…”
Section: Resultsmentioning
confidence: 50%
See 3 more Smart Citations
“…In our earlier metabolomics study of the VP16-02-003 and VP16-05-014, eighteen biomarkers were identified at t = 6 hours after the start of the light period [8]. In the present study, the rhythm of these biomarkers is followed during the circadian cycle.…”
Section: Resultsmentioning
confidence: 50%
“…The metabolic profiles for every time-point obtained by 1 H HR-MAS NMR were investigated by multivariate analysis of the bucket-reduced 1 H NMR data, as has been described in our earlier work [8]. In Fig 4, orthogonal partial least square discriminant analysis (OPLS-DA) was carried out to examine the variation in metabolic profile between two mutants and the wild-type Col-0 throughout the light/dark cycle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The significance of arabidopsis as a model system has led to several nuclear magnetic resonance (NMR)-based metabolomics studies with both solution and solid-state samples [14][15][16][17]. Recently developed approaches of 1 H high-resolution magic angle spinning NMR, which are circumventing the need for elaborate sample preparation and allowing utilization of solidstate NMR spectroscopy, were employed for the study of intact arabidopsis leaves [18,19]. NMR-based methods for studying plant metabolomics, including sample preparation protocols and data analysis approaches, are being refined continuously [20,21], contributing to a proliferation in their utilization.…”
Section: Introductionmentioning
confidence: 99%